Bulk properties of sediment core PS58/270-5 - Torben Struve; Frank Lamy; Frederik Gäng; Johann Philipp Klages; Gerhard Kuhn; Oliver Esper; Lester Lembke-Jene; Gisela Winckler (PANGAEA, 2025)
This dataset contains organic and inorganic bulk sediment properties for core PS58/270-5.
In: Struve, T et al. (2025): Sediment composition and particle flux reconstructions for the Southeast Pacific Antarctic Zone [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.982690